“The Sámi Exceptionalism”? Sámi People as inmates in Norwegian prisons: Ethnos and penitentiary policy: “The Sámi Exceptionalism”? Sámi People as inmates in Norwegian prisons: Ethnos and penitentiary policy (Archives of Criminology, 2023)
The Sámi are one of the three indigenous ethnic groups in Scandinavia, and more than half of the Sámi population lives in Norway. The special status of the Sámi in this country, and thus the legal solutions adopted by the Norwegian authorities, is a result of historical conditions, particularly the indigenous nature of this group. Particularly noteworthy are the rights granted to the Sámi in Sameloven – a law from 1987 that introduces the exceptional right of the Sámi to use their language while serving sentences in prison. The aim of this article is to present the rights of the Sami people as they are situated within Norwegian correctional facilities from three perspectives: theoretical, showcasing the key relevant legislative solutions; practical, pointing out violations of the rights of Sámi prisoners and Norway’s attempts to address these violations; and axiological, explaining the origin and philosophy of the special treatment of Sámi inmates in Norway (and, more broadly, of the Sámi People).